Plantární fibromatóza (Ledderhoseova nemoc) - Koudela, Karel; Koudela, Karel; Kunešová, Martina; Koudelová, Jana (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2010)
The authors describe the concomitant presence of plantar fibromatosis and Dupuytren's disease in a 33-year-old man. A lesion located under the sesamoid bones of the first metatarsophalangeal joint on the right showed an aggressive tendency (rapid growth, pain, impossibility to put weight on the medial side of the foot). Another lesion located proximal to the first one was smaller and painless. Neither plain radiography nor computed tomography showed any structural changes of the skeleton. Contrast-enhancement on magnetic resonance imaging revealed two lesions on the sole of the foot. Since a concurrence of plantar fibromatosis and malignant tumour could not be ruled out, an excision of both lesions and the adjacent plantar aponeurosis was made for biopsy examination. The operative procedure was carried out from two incisions. The intra-operative findings included proliferative growth and bleeding in the lesion located under the first metatarsophalangeal joint, and delimited growth without noticeable bleeding in the other lesion. Based on histological examination, the diagnosis of plantar fibromatosis was made for both lesions. The differential diagnosis and therapy of plantar fibromatosis is discussed.
Keywords: počítačová rentgenová tomografie; Magnetic Resonance Imaging; Adult; dospělí; magnetická rezonanční tomografie; Humans; nemoci nohy (od hlezna dolů); Dupuytren Contracture; mužské pohlaví; Fibroma; lidé; fibrom; Dupuytrenova kontraktura; Foot Diseases; Male; Tomography, X-Ray Computed